Implementation of a Digital-Based Community Complaint System in the Government of Posso Village, Ambon City - Amir Faisal Kotarumalos; Joana J Tuhumury; Nurainy Latuconsina (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2026)
The flow of globalization and the development of information technology encourage the government to adopt digital-based public services, including community complaint channels. This research aims to analyze the implementation of the digital complaint system in the Government of Passo Village, Teluk Ambon Baguala District, Ambon City, and to identify the challenges faced. The method used is a descriptive, qualitative approach through in-depth interviews, observation, and documentation. Data analysis applies the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The research results indicate that the digital complaint system has the potential to enhance transparency, accountability, and public participation. This system facilitates reporting access, accelerates follow-up actions, and provides structured data as a basis for policy formulation. However, its implementation still faces obstacles, including limited technological infrastructure, low public digital literacy, suboptimal capacity among officials, and a weak culture of public participation. These findings emphasize that the success of the digital complaint system at the village level requires a holistic approach that strengthens infrastructure, enhances officials' competence, develops digital literacy, and fosters a participatory culture. That integrative strategy is important so that the digital complaint system can function effectively in improving the quality of public services and local governance.